2020
DOI: 10.1111/1471-0528.16094
|View full text |Cite
|
Sign up to set email alerts
|

Baseline parameters for rotational thromboelastometry in healthy labouring women: a prospective observational study

Abstract: ObjectiveThe aim of this study was to establish rotational thromboelastometry (ROTEM®) baseline parameters in labouring women at term gestation. The secondary aim was to compare these reference ranges with those from previous studies on labouring women and from the manufacturer.DesignA prospective, observational study.SettingTertiary referral hospital.ParticipantsHealthy women in labour.MethodsEthics approval was granted for an opt‐out recruitment approach. ROTEM® testing was performed in labouring women at te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
4
8
1
Order By: Relevance
“…After the calculation of the median values in our study and their comparison with reference values for particular parameters obtained in non-pregnant population, we can state that all our results stayed in the reference range. On the contrary to the conclusions of the study of Lee et al [ 46 , 47 ], who confirmed higher amplitudes in studied individuals when compared with the non-pregnant population, in our study, the results stayed normal probably due to the use of the anticoagulant thromboprophylaxis. However, the reference ranges were determined in the non-pregnant population, so they could be evaluated in a different way using the ranges for the (high-risk) pregnant population.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…After the calculation of the median values in our study and their comparison with reference values for particular parameters obtained in non-pregnant population, we can state that all our results stayed in the reference range. On the contrary to the conclusions of the study of Lee et al [ 46 , 47 ], who confirmed higher amplitudes in studied individuals when compared with the non-pregnant population, in our study, the results stayed normal probably due to the use of the anticoagulant thromboprophylaxis. However, the reference ranges were determined in the non-pregnant population, so they could be evaluated in a different way using the ranges for the (high-risk) pregnant population.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, ROTEM may detect the hypercoagulable state associated with pregnancy [ 8 ]. Lee et al performed a prospective observational study of baseline parameters for ROTEM in healthy laboring women with uncomplicated pregnancy concluding that FIBTEM, EXTEM, and INTEM amplitudes were higher at term gestation than the determined reference ranges for the non-obstetric population [ 46 ]. The same authors evaluated baseline parameters of ROTEM in healthy pregnant women undergoing elective caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…externally valid in a more diverse US population 6,[13][14][15][16][17][18][19] . Establishment of valid reference ranges is the first step in implementing a goal-directed transfusion protocol.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This delay may in part be due to the significant complexity of the definition of PPH. Additionally, the adoption of VHAs in the PPH treatment may also be contributed to the lack of established transfusion trigger values, which have only been published recently [48][49][50]. A review of the timeline for the adoption of VHAs in trauma revealed a significant lag of approximately a decade which has been reproduced for PPH [3,12,25,[51][52][53][54][55][56][57][58][59][60].…”
Section: Historical Challenges In the Application Of Vhas For Pphmentioning
confidence: 99%
“…Studies have established a correlation between low fibrinogen levels and the incidence of PPH, but the low sensitivity and long turnaround time of this CCT make it insufficient for guiding BCT/HAT in PPH patients [71,72]. There is evidence in the utility of ROTEM in PPH as demonstrated by correlation between FIBTEM A5 and classical Clauss fibrinogen levels [48,73].…”
Section: Historical Challenges In the Application Of Vhas For Pphmentioning
confidence: 99%